Characterization of enantiomeric lignanamides from Solanum nigrum L. and their neuroprotective effects against MPP+-induced SH-SY5Y cells injury. (May 2019) - Li, Chen-Xi; Song, Xiao-Yu; Zhao, Wen-Yu; Yao, Guo-Dong; Lin, Bin; Huang, Xiao-Xiao; Li, Ling-Zhi; Song, Shao-Jiang
Abstract: Five pairs of enantiomeric lignanamides including nine undescribed compounds along with a known one were obtained from Solanum nigrum L. (Solanaceae). Their structures with absolute configurations were elucidated based on comprehensive spectroscopic analyses and quantum chemical calculations of electronic circular dichroism (ECD) curves. Additionally, all isolates were evaluated for their neuroprotective activity against MPP + (1-methyl-4-phenylpyridinium)-induced SH-SY5Y cells injury. Among them, cannabisin F showed the most significant neuroprotective effects at different concentrations (12.5, 25, 50  μ M). Further studies by Hoechst 33258 staining, monodansylcadaverine (MDC) staining and Annexin V/PI analysis demonstrated that cannabisin F could induce protective autophagy to protect SH-SY5Y cells from MPP + -induced apoptosis. Graphical abstract: Image 1 Highlights: Five pairs of enantiomeric lignanamides were isolated from Solanum nigrum L. Racemic mixtures were separated by chiral HPLC to obtain optically pure compounds. The absolute configurations of them were determined by computational ECD. Cannabisin F showed neuroprotective effects against SH-SY5Y cells injury. Cannabisin F could induce protective autophagy.